Implementation And Characterization Of Low Noise Amplifier At 4GHz Using RF Test Board - Zainal Mokhtar, Khursiah (Universiti Sains Malaysia, 2006)
The purpose of this project is to implement and characterize a single state Pseudomorphic High Electron Mobility Transistor (PHEMT) Low Noise Amplifier (LNA) at 4GHz. The LNA used in this project is Agilent’s MGA-72543 which has an operating frequency from 0.1 GHz to 6.0 GHz. This economical, easy-to-use GaAs MMIC Low Noise Amplifier (LNA) is designed for an adaptive CDMA receiver LNA and adaptive CDMA transmit driver amplifier. This LNA features a minimum noise figure of 1.4dB and 14dB associated gain from a single stage, feedback FET amplifier. It is housed in the SOT343 package and is part of the Agilent Technologies CDMA RF chipset. The quantities measured are input reflection coefficient, S11; gain, S21; noise figure, NF; P1 dB compression and input third-order intercept point, IIP3. The LNA has a bypass switch function on chip as well as an adjustable IIP3. The input of the MGA-72543 is internally optimally matched for a low noise figure. However, the input is additionally externally matched for a lower voltage standing wave ratio, VSWR. A simulation has also been performed. However, only the simulation on input reflection coefficient, S11; gain, S21 and noise figure, NF could be done by using Low Noise Amplifier S-parameter model the simulation against the linearity needs the usage of Low Noise Amplifier S-parameter large signal model. This particular model signal is not availabe in the ADS software. The characterization gives full insight into the performance of the GaAs Low Noise Amplifier scheme.